Aberrant Behaviors and Road Accidents among Iranian Truck Drivers, 2010 - Amir Houshang Mehrparvar; Seyyed Jalil Mirmohammadi; Abalfazl Barkhordari; Damon Ketabi (Tabriz University of Medical Sciences, 2011)
structural dimensions of which as well as technologic failures such as road quality, and tech-nical faults of automobiles, need to be assessed in detail. Iran has the first order in the world for deadly road accidents. This study was designed to assess the association between aberrant behaviors of truck drivers and the incidence of road accidents in Yazd, center of Iran, in 2010.Methods: This cross-sectional descriptive-analytic study was conducted on 300 truck drivers in Yazd. We used 3 questionnaires, including one for demographic data, Driver Behavior Questionnaire (DBQ), and one for drivers' self-evaluation of the of their driving.Results: Five types of the behavior had the highest frequency: Misjudge speed of oncoming vehicle when overtaking.; Deliberately disregard the speed limits late at night or very early in the morning.; Ignore 'give way' signs, and narrowly avoid colliding with traffic having right of way.; Stuck behind a slow-moving vehicle on a two-lane highway, you are driven by frustration to try to overtake in risky circumstances.; Drive with only 'half-an-eye' on the road while looking at a map, changing a cassette or radio channel, etc. The more the driver's driv-ing was influenced by emotional and mental states the more deliberate violations and slips.Conclusion: Among truck drivers, safety has not developed sufficiently, and because of the dangers of road accidents both for the drivers and other people and its economic losses, the importance of the presenting some solutions is completely obvious.